1984
DOI: 10.1007/bf00432036
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses to apomorphine and amphetamine in differentially housed mice

Abstract: The climbing response to apomorphine (AP, 0.075-3.0 mg/kg) and the motor activity response to amphetamine (AMP, 0,3-5.0 mg/kg) were determined in grouped or socially isolated mice. After 4 weeks of differential housing commencing at 5 weeks of age, the individually housed mice showed an increased response only to low doses of these drugs. The responses of the group-housed mice at 5 or 9 weeks of age were identical, ruling out an aging component to the differential responsiveness. Also, the response of separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Second, we observed a clear potentiation of the amphetamine hyperlocomotor response in male mice that is in agreement with previous mouse studies (Wilmot et al 1984(Wilmot et al , 1986. These findings in mice contrasted with the failure to obtain such an effect in Sprague-Dawley rats by Weiss et al (2001a).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Second, we observed a clear potentiation of the amphetamine hyperlocomotor response in male mice that is in agreement with previous mouse studies (Wilmot et al 1984(Wilmot et al , 1986. These findings in mice contrasted with the failure to obtain such an effect in Sprague-Dawley rats by Weiss et al (2001a).…”
Section: Discussionsupporting
confidence: 87%
“…The more robust effects of the isolation syndrome are: (1) increased spontaneous locomotor activity which often expresses in the form of habituation deficit (mice: Abramov et al 2004;Benton and Brain 1981;rats: Domeney and Feldon 1998;Gentsch et al 1988;Heidbreder et al 2000), with few exceptions limited to specific strains (Geyer et al 1993;Weiss et al 2000Weiss et al , 2001a; and (2) enhancement of the sensitivity to amphetamine (mice: Wilmot et al 1984Wilmot et al , 1986and rats: Jones et al 1990;Sahakian et al 1975;Smith et al 1997;Weiss et al 2001a). These findings are indicative of mesolimbic hyperdopaminergia (Dai et al 2004;Heidbreder et al 2000;Jones et al 1990;Leng et al 2004;Wilmot et al 1986), which is closely related to the genesis of positive symptoms in schizophrenia (e.g., Gray et al 1991;Laruelle et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Similar to the presmt findings in A/J mice, dopamine agonist-induced social-emotional reactivity was also observed at lower closes and at higher rates in isolated Institute for Cancer Research (ICR) mice than in group-housed ICR mice (Lewis et al 1994). Other studies have demonstrated that isolated animals were more sensitive to the motor stimulant effects of apomorphine (Sahakian et al 1975;Wilmot et al 1984Wilmot et al , 1986, amphetamine (Ahmed et al 1995;Jones et al 1990;Lewis et al 1990;Sahakian et al 1975;Wilmot et al 1984Wilmot et al , 1986, and cocaine (Phillips et al 1994) than animals reared in groups. The effects of amphetamine on acoustic startle have been also shown to be more pro-nounced in isolated rats (Kokkinidis and MacNeill 1982).…”
Section: Discussionsupporting
confidence: 66%
“…Evidence has now accumulated indicating that social isolation produces alterations in dopaminergic function. When compared to group-housed animals, isolated animals have been characterized by enhanced sensitivity to the stereotypic and motor effects of cl-amphetamine and apomorphine (Ahmed et al 1995;Guisado et al 1980;Jones et al 1990Jones et al , 1992Lewis et al 1990;Sahakian et al 1975;Wilmot et al 1984Wilmot et al , 1986. The effects of cl-amphetamine on acoustic startle response have also been found to be greater in isolated animals (Kokkinidis and MacNeill 1982).…”
mentioning
confidence: 99%
“…Rats individually housed for prolonged periods, 12-15 months, had an increased number of striatal 3H-spiroperidol binding sites (Guisado et al 1980). We have previously reported that differentially housed mice show changes in the baseline motor activity and the behavioral responses to APO and AMP suggestive of a state of behavioral facilitation, or an autoreceptor subsensitivity (Wilmot et al 1984). The present studies were conducted to consider further the differences in the presynaptic and postsynaptic regulation of DA function that occur with differential housing.…”
mentioning
confidence: 99%